Incremental and decremental L- and M-cone driven ERG responses: II. Sawtooth stimulation - Kremers, Jan; Pangeni, Gobinda; Tsaousis, Konstantinos; Mckeefry, Declan; Murray, Ian J.; Parry, Neil R. A. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2014)
L- and M-cone driven on- and off-ERG responses and their interactions were examined using full field stimuli with sawtooth temporal profiles. The effects of temporal frequency and contrast were studied. ERG recordings were obtained from 21 trichromatic, 1 protanopic, and 1 deuteranopic subjects. ERGs to L-cone increments and decrements resembled those to M-cone decrements and increments, respectively (i.e., of the opposite polarity). Temporal frequency and contrast had little effect on the implicit times. All response components varied linearly with contrast. When stimulated simultaneously, the responsivities of most components were larger for counterphase than for inphase modulation. The retinal processing leading to an ERG response is reversed for L-and M-cone driven responses. (c) 2014 Optical Society of America